The issue of polycultural competence formation in Ukraine and Chine - Iryna Glazkova (Kazimierz Wielki University, 2021)
The article deals with the search of the effective ways of the students' polycultural competence formation process at Chinese and Ukrainian universities. The analysis of Ukrainian and Chinese scientists' view scientific papers, give us possibility to state that polycultural competence is an integrative personal formation that includes the knowledge, skills, traits and values of a person. Polycultural competence facilitates one's ability to interact effectively with representatives of other cultures on the basis of mutual respect, understanding and tolerance as well as the willingness to continue and to develop the diversity of cultural self-expressions in the context of a globalized society. The author proves that the basis of the polycultural competence formation is a foreign language. The effectiveness of such method as: reading, direct method, method of analogy and purposeful and practical methods in the process of polycultural competence formation while teaching foreign languages in higher education institutions inUkraineand Chine are described.